Chemoprevention of Gastric Cancer: Helicobacter pylori Eradication - Eun Jin Kim; Hang Lak Lee (Yong Chan Lee, 2017)
Gastric cancer is one of the most common fatal malignancies in the world, with a high incidence in Korea and Japan. Helicobacter pylori infection is an important factor in the pathogenesis of gastric cancer. Epidemiological studies have shown a strong causal relationship between H. pylori infection and gastric cancer. Animal studies have also shown that eradication of H. pylori infection, especially at the early stage, is effective in preventing H. pylori-related gastric carcinogenesis. H. pylori eradication leads to regression and prevents the progression of gastric precancerous lesions but only in a minority of cases. H. pylori eradication appears to be the most promising approach for gastric cancer prevention. The current available data from human studies show that H. pylori eradication can reduce the risk of developing gastric cancer, and this strategy is more useful in patients without atrophic gastritis or intestinal metaplasia. A longer follow-up and additional studies are needed for a better understanding of this issue.